Effects of sacubitril/valsartan in patients with a systemic right ventricle: early evidence of exercise tolerance and systolic function improvement. (14th October 2021) - Fusco, F; Merola, A; Scognamiglio, G; Palma, M; Correra, A; Barracano, R; Borrelli, N; Grimaldi, N; Spinelli Barrile, C; Puzone, N; Ciriello, G D; Colonna, D; et al.
Abstract: Background: Sacubitril/valsartan has been shown to reduce mortality and morbidity inpatients with heart failure and reduced systolic function. However, the effects of this novel association in patients with congenital heart disease and a systemic right ventricle (sRV) have not been investigated yet. Purpose: We aimed to assess tolerability and efficacy of sacubitril/valsartan in patients with a sRV Methods: From September 2020 to March 2021, 38 patients with congenitally corrected transposition of the great arteries or transposition of the great arteries after Senning or Mustard repair were prospectively enrolled. Inclusion criteria were: age ≥18 years, optimal medical therapy including ACEi/ARB for at least 6 months and EF of the sRV ≤40%. Patients with univentricular physiology, systolic blood pressure (SBP) <90mmHg, glomerular filtration rate (GFR) <30ml/min or K >5.5mEq/L were excluded. RV systolic function was assessed on echocardiography using a multiparametric evaluation. The study protocol contemplates serial assessments at 1, 3, 6 and 12 months after treatment initiation. Results: Up to March 31th, 23 patients completed 1-month and 15 completed 3-month assessment after treatment initiation. Baseline patients' characteristics are summarized in table 1. The medication dose was up-titrated to the highest tolerated dose during follow-up. During early follow-up, no major adverse events were reported. Treatment did not impact significantly on the values of serum potassium (basal K+ 4.4 [4.2–4.6] mEq/L, K+ at 3 months 4.4 [4.3–4.6] mEq/L, p=0.7) and GFR (basal GFR 113.9±35ml/min, GFR at 3 months 107.8±21 ml/min, p=0.7). Although SBP did not change significantly (114±12 vs 113.9±19 mmHg at 1-month and 117.3±12 mmHg at 3 months; p=0.9 for both), 2 (5%) patients ceased the treatment due to symptomatic hypotension during the first month of treatment. There was no significant change in the NYHA class. However, the 6-minute walking distance increased significantly after 3 months (365±120 vs 498.3±71 min; p=0.01). Furthermore, while traditional echocardiographic parameters of RV systolic function (TAPSE, s wave and FAC) did not change significantly, RV global longitudinal strain (GLS) and RV free wall GLS demonstrated subclinical improvement in right ventricular systolic function (table 2). Conclusions: Our short-term results from an ongoing prospective study showed that sacubitril/valsartan is well tolerated in patients with a sRV with early evidence of improvement in exercise tolerance and sRV systolic function. Longer follow-up is warranted to confirm these data. Funding Acknowledgement: Type of funding sources: None.